71.8k views
0 votes
By Substitution
-6x + 6y = 6
-6x + 3y = -12

2 Answers

2 votes

Answer:

x = 5 & y = 6

Explanation:

hi see the pic for the steps

By Substitution -6x + 6y = 6 -6x + 3y = -12-example-1
User Shicky
by
5.4k points
1 vote

Answer:

y=6

x=5

Explanation:

multiply first equation by -1

-1 × -6x + 6y =6 ➡ 6x -6y = -6 now add up both equations

6x-6y -6x+3y = -6-12 (6x will be eliminated)

-3y = -18

y=6 use this value to find x

-6x +6×6=6 ➡ -6x = 6 -36 ➡x = 5

User Xrstf
by
5.2k points